Towards sustainable co-management organization: a case study of the Baikka Beel, Moulvibazar, Bangladesh - Shahidul Islam Bhuiya (Journal of Fisheries, 2014)
The present study was conducted in Baikka Beel, Moulvibazar, Bangladesh from July, 2012 to October, 2012. This paper examined the role and performance of the CMOs in the Beel management and the challenges faced by the CMO members. Primary information were collected through focus group discussions using conceptual framework. Organizational development, leadership development, capital formation, women and gender development and conflict resolution were used to examine the performance of the CMOs. The result revealed that the RMO and FRUG were in satisfactory level in sustainability except RMO network. However CMOs were facing some challenges. These included policy level (amendment of Fish Act 1950 regarding permanent sanctuary, lease period extension complexity, no national and social recognition of CMO members, less awareness program to the non-CMO respondents, few scope of media highlight and no fund especially in RMO network operation) and operational level (no vehicle to rush to protect the poaching, no provision of honorary for RMO members, less training in capacity building and regional and statewide interactions). At last some recommendations were made for both policy and operational level. Finally new project could be implemented through the implementation of the research findings towards sustainable CMOs.